2019
DOI: 10.15430/jcp.2019.24.2.123
|View full text |Cite
|
Sign up to set email alerts
|

Esculetin Prevents the Induction of Matrix Metalloproteinase-1 by Hydrogen Peroxide in Skin Keratinocytes

Abstract: Background Reactive oxygen species (ROS) are involved in various cellular diseases. Excessive ROS can cause intracellular oxidative stress, resulting in a calcium imbalance and even aging. In this study, we evaluated the protective effect of esculetin on oxidative stress-induced aging in human HaCaT keratinocytes. Methods Human keratinocytes were pretreated with esculetin for 30 minutes and treated with H 2 O 2 . The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…JNK phosphorylation induces the activation of downstream transcription factor proteins, including AP-1 protein [ 45 ]. AP-1 activation is critical for MMP synthesis [ 47 ]. In our study, we investigated AP-1 activation by evaluating the activation of c-Jun and c-Fos proteins, which are two main components of the AP-1 complex.…”
Section: Discussionmentioning
confidence: 99%
“…JNK phosphorylation induces the activation of downstream transcription factor proteins, including AP-1 protein [ 45 ]. AP-1 activation is critical for MMP synthesis [ 47 ]. In our study, we investigated AP-1 activation by evaluating the activation of c-Jun and c-Fos proteins, which are two main components of the AP-1 complex.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, it has been reported that Esc can improve oxidative stress and apoptosis in H9c2 cells by reducing the phosphorylation level of JNK in order to attenuate myocardial ischemia/reperfusion (I/R) injury [28]. In addition, Esc can protect oxidative stress-induced aging in human HaCaT keratinocytes by decreasing the phosphorylation level of c-Jun and c-Fos and inhibiting the JNK signaling pathway [29]. Thus, we hypothesized that the protective effect of Esc in H 2 O 2 -induced HepG2 cells might be closely associated with the JNK signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that H 2 O 2 upregulates the expression of MMP-1, thus promoting skin aging and oxidative stress by activating the MAPK and AP1 signaling pathways. The treatment of 5 µg/mL esculetin to H 2 O 2 -induced oxidative stress in HaCaT cells results in the inhibition of MMP-1, phospho-MEK1, phospho-ERK1/2, phospho-SEK1, and phospho-JNK1/2 along with the intracellular Ca 2+ levels [ 62 ]. In addition, esculetin at 50 µL was reported to protect human fibroblast from oxidative stress-induced DNA damage induced by linoleic acid hydroxide and iron (III) ion [ 63 ] ( Table 2 , Figure 3 ).…”
Section: Therapeutic Applications Of Esculetinmentioning
confidence: 99%